Monatomic catalyst with high metal loading capacity and good atom dispersity and preparation method

The nanofiber membranes are prepared by electrospinning and high-temperature treatment is carried out in high-temperature resistant devices, which solves the problems of low metal content and uncontrollable metal load in single atomic catalysts, and achieves efficient and uniform single atomic catalyst preparation.

CN120231075APending Publication Date: 2025-07-01JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311831999.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing single-atom metal catalyst has low metal content, resulting in low catalytic efficiency. In conventional preparation methods, the gaseous metal reacts unevenly with carbon and nitrogen materials, and the metal load is uncontrollable.

Method used

Nanofiber films were prepared by electrospinning the spinning liquid containing metal salt, and placed them between two high-temperature resistant devices, pre-oxidation, carbon thermal reduction and vapor deposition, and finally taken out from the high-temperature resistant device to prepare a single-atom catalyst with high metal load and good atomic dispersion.

Benefits of technology

The high metal loading and uniformity of atomic distribution of single atomic catalysts are achieved, the catalytic efficiency is significantly improved, and the metal content is controllable, which is much higher than the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120231075A_ABST
    Figure CN120231075A_ABST
Patent Text Reader

Abstract

The invention discloses a monatomic catalyst with high metal loading capacity and good atom dispersity and a preparation method, and belongs to the field of monatomic material preparation. The method for preparing the monatomic catalyst with high metal loading capacity and good atom dispersity comprises the following steps: (1) mixing metal salt, a polymer and a solvent to obtain a spinning solution; performing electrostatic spinning to obtain a nanofiber membrane; wherein the molar ratio of the metal salt to the polymer is (1: 5)-(1: 20); and (2) placing the nanofiber membrane between two layers of high-temperature-resistant devices, carrying out pre-oxidation, carbon thermal reduction and vapor deposition, and then taking out the nanofiber membrane from the high-temperature-resistant devices, thereby obtaining the monatomic catalyst with high metal loading capacity and good atomic dispersity. According to the method disclosed by the invention, the multi-layer simultaneous calcination of the nano-cellulose membrane can be realized by adopting the high-temperature-resistant device on multiple layers, so that the efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a single-atom catalyst with a high metal loading and good atomic dispersion and a preparation method thereof, belonging to the field of single-atom material preparation. Background Art

[0002] For a long time, the scientific research community has made a series of remarkable progress in the research of metal nanoparticle catalysts. Nevertheless, due to the limited intrinsic activity of such catalysts, scientists have gradually turned to the research and development of smaller-scale metal nanoparticles, clusters or single-atom catalysts in the hope of obtaining better catalytic activity at a lower scale. When the metal structure on the catalyst surface gradually transitions from nanoparticles to nanoclusters and then to the atomic level, its catalytic performance exhibits very interesting and important variation characteristics.

[0003] Traditional metal catalysts are usually troubled by the problem of low metal utilization rate. One of the main reasons is that a large number of bulk metal atoms only play the role of "spectators" in the heterogeneous catalytic process and cannot truly participate in the reaction. Therefore, how to improve the metal utilization rate to reduce the cost of the catalyst and improve the efficiency has become a hot research topic in the catalytic field. And improving the dispersion of metal atoms in the catalyst is the key means to achieve this goal.

[0004] A single-atom catalyst is composed of isolated metal atoms and a solid support. Its remarkable characteristic is that the atomic utilization rate is extremely high and it has a definite active center; this catalyst can exhibit unique reaction properties caused by the size effect; these isolated metal active sites are stabilized by chemical bonding with specific coordination atoms on the solid support. In addition, in addition to the advantage of high atomic utilization rate, the single-atom catalyst is particularly important due to the spatial isolation between its metal center and the support and the strong influence of the support on the catalytic performance.

[0005] In the actual heterogeneous catalytic process, all reactions occur at the active sites on the solid surface. Therefore, increasing the proportion of surface-active metal atoms can significantly enhance the catalytic efficiency. However, it should be noted that zero-valent metals in the single-atom state are very unstable and usually need to be stabilized by specific atoms (such as O, C, N, S, P, etc.) on the solid host material.

[0006] At present, some researchers prepare single-atom catalysts through electrospinning, pre-oxidation, and high-temperature carbonization. For example, Patent CN 116850997A discloses a carbon nanofiber-supported single-atom nickel catalyst and its preparation method, which dissolves a nickel precursor in a spinning solution and then prepares nanofibers by electrospinning the spinning solution. Subsequently, the nanofibers are placed in a tube furnace for pre-oxidation and high-temperature carbonization to obtain a carbon nanofiber-supported single-atom nickel catalyst. However, the mass of nickel is 0.01-0.1 wt% of the mass of the electrospinning precursor. Patent CN 116870908A discloses a carbon nanofiber-supported single-atom copper catalyst and its preparation method, which dissolves a copper precursor in a spinning solution and then prepares nanofibers by electrospinning the spinning solution. Subsequently, the nanofibers are placed in a tube furnace for pre-oxidation and high-temperature carbonization to obtain a carbon nanofiber-supported single-atom copper catalyst. However, the mass of copper in the copper precursor is 0.01-0.1 wt% of the mass of the electrospinning precursor. Summary of the Invention

[0007] [Technical Problem]

[0008] In existing single-atom metal catalysts, the low metal content leads to low catalytic efficiency.

[0009] In the conventional gas-phase deposition used for preparing single-atom catalysts, there are problems such as uneven reaction between gaseous metals and carbon-nitrogen materials and uncontrollable metal loading.

[0010] [Technical Solution]

[0011] To solve the above problems, in the present invention, a nanofiber membrane is first prepared by electrospinning a spinning solution containing a metal salt. Subsequently, the nanofiber membrane is placed between two high-temperature-resistant devices, followed by pre-oxidation, carbothermal reduction, and gas-phase deposition. Finally, the single-atom catalyst supported on carbon nanofibers is taken out from the high-temperature-resistant device. The single-atom catalyst prepared by the present invention has a high metal content and uniform atomic distribution.

[0012] The first object of the present invention is to provide a method for preparing a single-atom catalyst with a high metal loading and good atomic dispersion, comprising the following steps:

[0013] (1) Mix a metal salt, a polymer, and a solvent to obtain a spinning solution; then obtain a nanofiber membrane by electrospinning. Among them, the molar ratio of the metal salt to the polymer is 1:5-1:20.

[0014] (2) Place the nanofiber membrane between two high-temperature-resistant devices, perform pre-oxidation, carbothermal reduction, and gas-phase deposition, and then take it out from the high-temperature-resistant device to obtain a single-atom catalyst with a high metal loading and good atomic dispersion.

[0015] In one embodiment of the present invention, the metal in the metal salt in step (1) is one of iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, platinum, palladium, iridium, chromium, manganese, tungsten, vanadium, etc.

[0016] In one embodiment of the present invention, when the molar ratio of the metal salt to the polymer in step (1) is 1:10, the metals in the metal salt are chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), and nickel (Ni), etc.

[0017] In one embodiment of the present invention, the range of the molar ratio of the metal salt to the polymer in step (1) exists because different metal salts may have different chemical and physical properties. Optimizing within the range of 1:5 - 1:20 can basically obtain the spinning solution and effectively prepare the corresponding nanofiber membrane.

[0018] In one embodiment of the present invention, the metal salt in step (1) is one of chloride salts, nitrate salts, sulfate salts, and carbonate salts.

[0019] In one embodiment of the present invention, the polymer in step (1) is one or several of flexible polymers such as polyester (PCL), polyamide (PA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and polyacrylonitrile (PAN).

[0020] In one embodiment of the present invention, when the polymer is polyacrylonitrile in step (1), the ratio of 0.1 g of metal salt to 2 g of polyacrylonitrile can effectively prepare a high-quality nanofiber membrane. This specific ratio is determined based on a comprehensive consideration of the physical and chemical properties of polyacrylonitrile and its interaction with the metal salt.

[0021] In one embodiment of the present invention, the solvent in step (1) is one or several of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), chloroform, tetrahydrofuran (THF), ethanol, water, etc.

[0022] In one embodiment of the present invention, the mass ratio of the polymer to the solvent in step (1) is 1:5 - 20, and further preferably 1:10.

[0023] In one embodiment of the present invention, the parameter settings for electrospinning in step (1) are as follows: the receiving distance is 15 - 20 cm; the flow rate is 0.2 - 0.8 mL / h; the voltage is 15 - 22 kV; the spinning volume is 1.5 - 4.2 mL; the temperature is 30 - 60 °C; the humidity is 40 - 60%; the inner diameter of the spinneret is 0.5 - 1.5 mm.

[0024] In one embodiment of the present invention, the high-temperature resistant device in step (2) is one of graphite devices, quartz devices, and ceramic devices.

[0025] In one embodiment of the present invention, the high-temperature resistant device in step (2) is in a sheet shape and forms a sandwich structure with the nanocellulose membrane.

[0026] In one embodiment of the present invention, the high-temperature resistant device in step (2) can be laid at intervals with the nanocellulose membrane to form a multi-layer structure.

[0027] In one embodiment of the present invention, the high-temperature resistant device in step (2) is composed of a single layer or multiple layers of special materials that can withstand the high-temperature conditions during pre-oxidation, carbothermal reduction, and chemical vapor deposition; these layers have a high degree of airtightness and can effectively encapsulate the nanofiber membrane while maintaining a certain gas permeability to allow specific gases such as oxygen (O2) and argon (Ar) to enter during necessary process steps; this semi-closed environment is the key to achieving a high metal loading and excellent atomic dispersion because it allows precise chemical reactions to occur while preventing damage or contamination of the nanofiber membrane during processing.

[0028] In one embodiment of the present invention, the high-temperature resistant device in step (2) adopts a sheet design and forms a sandwich-like structure together with the nanofiber membrane. The high-temperature resistant device can be alternately laid with the nanofiber membrane to form a multi-layer composite structure. This unique structure not only enhances the stability of the overall structure but also provides additional flexibility to adapt to different processing conditions and catalytic performance requirements. Through this design, the metal loading and atomic dispersion of the single-atom catalyst can be significantly improved, providing an ideal platform for efficient catalytic reactions.

[0029] In one embodiment of the present invention, the pre-oxidation, carbothermal reduction, and chemical vapor deposition in step (2) are carried out in a quartz tube in a tube furnace.

[0030] In one embodiment of the present invention, in step (2), the pre-oxidation is heated to 210 - 280 °C at a rate of 2 - 10 °C / min and kept at a constant temperature for 1 - 3 h.

[0031] In one embodiment of the present invention, in step (2), the carbothermal reduction and chemical vapor deposition are carried out under the atmosphere of a protective gas (argon, helium, nitrogen, or hydrogen) by calcination treatment; specifically, the temperature is heated to 800 - 1200 °C (the temperature for metal vaporization) at a rate of 2 - 5 °C / min and kept at a constant temperature for 1 - 5 h (to complete the process of uniform atomic diffusion).

[0032] The second object of the present invention is a single-atom catalyst with a high metal loading and good atomic dispersion prepared by the method of the present invention.

[0033] The third object of the present invention is a method for synthesizing ammonia by nitrate reduction, which uses the single-atom catalyst with high metal loading and good atomic dispersion described in the present invention.

[0034] The fourth object of the present invention is the application of the single-atom catalyst with high metal loading and good atomic dispersion described in the present invention in the fields of electrolytic water, carbon dioxide reduction to prepare methanol, nitrate reduction to ammonia, or carbon-nitrogen coupling to prepare urea.

[0035] The fifth object of the present invention is to provide a method for improving the metal loading and uniformity of a single-atom catalyst, including the following steps:

[0036] (1) Mix a metal salt, a polymer, and a solvent to obtain a spinning solution; then obtain a nanofiber membrane by electrospinning; wherein, the molar ratio of the metal salt to the polymer is 1:5 - 1:20;

[0037] (2) Place the nanofiber membrane between two layers of high-temperature resistant devices, perform pre-oxidation, carbothermal reduction, and chemical vapor deposition, and then take it out from the high-temperature resistant devices to obtain a single-atom catalyst with high metal loading and good atomic dispersion.

[0038] [Beneficial effects]

[0039] (1) In the present invention, the electrospun nanofiber membrane is used as the source of carbon and nitrogen materials, and the metal salt can be uniformly and densely distributed on the electrospun fibers; the electrospun nanofibers have the advantages of large aspect ratio, large specific surface area, and high porosity. During the chemical vapor deposition process, due to the sealing and blocking effects of the high-temperature resistant devices and the excellent heat conduction of the devices themselves, the electrospun nanofibers can be fully contacted with the gaseous metal. Moreover, because of the sealing of the high-temperature resistant devices, the nanofiber membrane per unit area can be controlled to perform carbothermal reduction with a quantitative amount of gaseous metal salt on the membrane, and the amount of the metal salt, together with the area and thickness of the nanofiber membrane, jointly determines whether a catalyst mainly composed of single atoms is finally formed.

[0040] (2) The single-atom catalyst prepared by the present invention has a high metal content and uniform atomic distribution.

[0041] (3) The mass of the metal salt used in the present invention can account for more than 5% of the total mass of the catalyst at most (tested by inductively coupled plasma technology (ICP)), and its metal content is much higher than the current methods for preparing single-atom catalysts.

[0042] (4) The method of the present invention can achieve the simultaneous calcination of multiple layers of nanocellulose membranes by using multiple layers of high-temperature resistant devices, greatly improving the efficiency.

[0043] (5) The high-temperature resistant devices used in the present invention have the following functions:

[0044] A: Sealing and protecting the nanofiber membrane. The ultra-thin nanofiber membrane is sealed to effectively protect the fiber membrane from direct damage or contamination during the high-temperature treatment process.

[0045] B: Withstanding extreme high-temperature conditions. The high-temperature-resistant device is composed of multiple layers of special high-temperature-resistant materials and can withstand extreme high-temperature environments during steps such as pre-oxidation, carbothermal reduction, and chemical vapor deposition.

[0046] C: Allowing the permeation of key gases. Although the high-temperature-resistant device has high tightness, it can also allow key gases such as oxygen (O2) and argon (Ar) to permeate during necessary process steps, which is very important for achieving precise chemical reactions.

[0047] D: Sandwich structure design. The high-temperature-resistant device adopts a sheet design and forms a sandwich structure together with the nanofiber membrane. This structure not only increases the stability during the treatment process but also helps to maintain the uniformity and integrity of the nanofiber membrane.

[0048] E: Forming a multi-layer composite structure. The high-temperature-resistant device can be laid at intervals with the nanofiber membrane to form a multi-layer structure, providing additional physical support and also being able to adjust the performance of the catalyst as needed.

[0049] F: Improving the performance of the catalyst. The high-temperature-resistant device significantly improves the metal loading and atomic dispersion of the single-atom catalyst, providing ideal conditions for efficient catalytic reactions. Description of the Drawings

[0050] Figure 1 Scanning electron microscope photograph of the nickel single-atom catalyst prepared in Example 1.

[0051] Figure 2 Transmission electron microscope photograph of the nickel single-atom catalyst prepared in Example 1.

[0052] Figure 3 Aberration-corrected electron microscope photograph of the nickel single-atom catalyst prepared in Example 1.

[0053] Figure 4 EDS mapping photograph of the nickel single-atom catalyst prepared in Example 1.

[0054] Figure 5 X-ray diffraction pattern of the nickel single-atom catalyst prepared in Example 1.

[0055] Figure 6 Scanning electron microscope photograph of the copper single-atom catalyst prepared in Example 2.

[0056] Figure 7TEM image of the copper single-atom catalyst prepared in Example 2.

[0057] Figure 8 AC-STEM image of the copper single-atom catalyst prepared in Example 2.

[0058] Figure 9 EDS mapping images of the copper single-atom catalyst prepared in Example 2.

[0059] Figure 10 XRD pattern of the copper single-atom catalyst prepared in Example 2. Detailed implementation manners

[0060] The following are preferred embodiments of the present invention. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0061] In the examples and comparative examples, unless otherwise specified, the experimental methods used are all conventional methods, and the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial channels.

[0062] Example 1

[0063] A method for preparing a nickel single-atom catalyst with high metal loading and good atomic dispersion, comprising the following steps:

[0064] (1) Add 2 g of PAN, 20 g of DMF and 0.1 mmol of NiCl₂ into a 50 mL glass bottle, then add a magnetic stir bar with a radius of 1 cm, stir at room temperature for 10 h to obtain a spinning solution; perform electrospinning on the spinning solution, control the distance between the spinneret and the receiving plate to be 20 cm, the flow rate of the spinning solution to be 0.36 mL / L, the diameter of the spinneret to be 0.7 mm, apply a positive electrostatic pressure of 20 KV to the spinneret, receive through aluminum foil, and then place the aluminum foil containing the nanofiber membrane in an oven at 60 °C for 10 h to dry, and remove it from the aluminum foil to obtain a nanofiber membrane (a circular shape with a diameter of 10 cm);

[0065] (2) Cut the nanofiber membrane and place it between two graphite devices (sized 30 cm * 1 cm, with a thickness of 1 mm in sheet form), and then place the nanofiber membrane and the graphite devices in a quartz tube in a tube furnace; heat at a rate of 2 °C / min to 230 °C and keep it at a constant temperature for 3 h for pre-oxidation, in an argon atmosphere, heat from 230 °C to 1000 °C at a rate of 2 °C / min and keep it at a constant temperature for 4 h for carbothermal reduction and vapor deposition, in an argon atmosphere, cool from 1000 °C to room temperature, and cool at room temperature; take it out from the graphite device to obtain a nickel single-atom catalyst supported on carbon nanofibers, that is, a nickel single-atom catalyst with high metal loading and good atomic dispersion.

[0066] The obtained catalyst was subjected to performance tests, and the test results are as follows:

[0067] Figure 1 This is a scanning electron microscope (SEM) image of the nickel single-atom catalyst prepared in Example 1. From Figure 1 it can be seen that the image shows a well-structured nanofiber network with a diameter of approximately 100 nm. The fibers exhibit a high degree of uniformity and are intertwined to form a porous matrix, indicating a large surface area available for catalytic reactions. Notably, no visible metal particles are observed at this scale, suggesting that nickel atoms are atomically dispersed on the carbon fiber surface. This dispersion is characteristic of single-atom catalysts (SACs), where metal atoms are isolated and individually distributed, avoiding the formation of clusters or nanoparticles that are typically observable by SEM at this magnification. This atomic-level dispersion is expected to provide excellent exposure of active nickel sites, potentially leading to a significant increase in catalytic efficiency due to maximized surface interactions with reactants. The morphological characteristics of the nanofiber network, combined with the atomic dispersion of nickel, provide strong indication of the material's suitability for catalytic applications where high surface area and availability of active sites are crucial.

[0068] Figure 2 This is a transmission electron microscope (TEM) image of the nickel single-atom catalyst prepared in Example 1. From Figure 2 it can be seen that no visible metal particles are present, indicating that the possible nickel single-atom catalyst has achieved a high degree of dispersion on the fiber surface.

[0069] Figure 3 This is a spherical aberration-corrected electron microscope (AC-STEM) image of the nickel single-atom catalyst prepared in Example 1. Figure 3 The bright dot-like features observed are consistent in size with individual nickel atoms, and these features do not coalesce into larger particles or clusters, indicating atomic-level dispersion.

[0070] Figure 4 This is an energy-dispersive X-ray spectroscopy (EDS) mapping image of the nickel single-atom catalyst prepared in Example 1. From Figure 4 it can be seen that the signal of the nickel (Ni) element shows a highly uniform distribution on the support structure. The uniform distribution of the nickel signal indicates that its dispersion on the support has reached the single-atom level, with no obvious clustering or granulation, which strengthens the evidence of the high dispersion of the single-atom catalyst. The carbon (C) and nitrogen (N) signals in the mapping further confirm the composition of the support and the possible interactions between nickel atoms and these two elements in the support.

[0071] Figure 5 This is the X-ray diffraction (XRD) pattern of the nickel single-atom catalyst prepared in Example 1. From Figure 5It can be seen that the broadened peak may indicate the amorphous or nanocrystalline characteristics of the support material, rather than the influence of metal particles. This further supports the view that metal atoms are dispersed on the support in the form of single atoms.

[0072] Example 2

[0073] A method for preparing a copper single-atom catalyst with a high metal loading and good atomic dispersion, comprising the following steps:

[0074] (1) Add 2 g of PAN, 20 g of DMF, and 1 mmol of CuCl2 into a 50 mL glass bottle, then add a magnetic stirrer with a radius of 1 cm, and stir at room temperature for 10 h to obtain a spinning solution; perform electrospinning on the spinning solution, control the distance between the spinneret and the receiving plate to be 20 cm, the flow rate of the spinning solution to be 0.36 mL / L, the diameter of the spinneret to be 0.7 mm, apply a positive electrostatic pressure of 20 KV to the spinneret, receive through aluminum foil, and then place the aluminum foil containing the nanofiber membrane in an oven at 60 °C for drying for 10 h, remove it from the aluminum foil to obtain a nanofiber membrane (the size of the membrane is a circular shape with a diameter of 10 cm);

[0075] (2) Place the nanofiber membrane between two graphite devices (size: 30 cm * 1 cm, thickness: 1 mm, sheet-like), and then place the nanofiber membrane and the graphite devices in a quartz tube in a tubular furnace; heat up to 230 °C at a rate of 2 °C / min and keep it at a constant temperature for 3 h for pre-oxidation, under an argon atmosphere, heat up from 230 °C to 1000 °C at a rate of 2 °C / min and keep it at a constant temperature for 4 h for carbothermal reduction and vapor deposition, cool down from 1000 °C to room temperature under an argon atmosphere, and cool at room temperature; take it out from the graphite device to obtain a nickel single-atom catalyst supported on carbon nanofibers, that is: a copper single-atom catalyst with a high metal loading and good atomic dispersion.

[0076] Perform performance testing on the obtained catalyst, and the test results are as follows:

[0077] Figure 6 It is a scanning electron microscope photo of the copper single-atom catalyst prepared in Example 2. From Figure 6 It can be seen that it shows a structurally uniform nanofiber network with a diameter of approximately 100 nanometers. The uniform distribution of the fibers and the porous structure formed by them imply a high surface area that is crucial for catalytic activity. More importantly, no obvious metal aggregates are found in the image, indicating that copper atoms may achieve a high degree of atomic dispersion on the support. This atomic-level copper dispersion is expected to expose a large number of active sites, thus possibly greatly improving the catalytic efficiency. These characteristics indicate the potential applicability of this material in catalytic applications where active sites need to be easily accessible.

[0078] Figure 7TEM image of the copper single-atom catalyst prepared in Example 2. It can be seen from Figure 7 that there are no obvious metal particle accumulations on the fiber surface, which further confirms that copper atoms may have been dispersed to the single-atom scale on the carrier surface.

[0079] Figure 8 HAADF-STEM image of the copper single-atom catalyst prepared in Example 2. It can be seen from Figure 8 the high-resolution image taken by the aberration-corrected transmission electron microscope that the existence of copper single atoms on the carrier is revealed. The bright spots shown in the image match the expected size of individual copper atoms, and the dispersion state of these bright spots does not form large clusters, indicating atomically dispersed copper atoms.

[0080] Figure 9 EDS mapping image of the copper single-atom catalyst prepared in Example 2. It can be seen from Figure 9 the energy-dispersive X-ray spectroscopy that the uniform distribution of copper elements on the carrier is revealed, strengthening the high dispersion of the single-atom catalyst. The distribution of carbon and nitrogen signals also shows the composition of the carrier and the possible interaction between copper atoms and these elements in the carrier.

[0081] Figure 10 XRD pattern of the copper single-atom catalyst prepared in Example 2. It can be seen from Figure 10 the lack of obvious characteristic peaks of the metal crystal phase that the carrier material is amorphous or nanocrystalline, rather than being affected by metal particles. The broad peaks may represent the amorphous characteristics of the carrier material, further supporting the view that copper atoms have been dispersed in the form of single atoms on the carrier surface.

[0082] Comparative Example 1

[0083] Adjust the dosage of CuCl2 in Example 2 to 5 mmol, and keep other conditions the same as in Example 2 to obtain a copper particle catalyst supported on carbon nanofibers.

[0084] It is found that excessive dosage of CuCl2 cannot obtain a single-atom catalyst.

[0085] Comparative Example 2

[0086] Omit the graphite device in Example 2, and directly place the obtained nanofiber membrane in a quartz tube in a tube furnace for pre-oxidation, carbothermal reduction and chemical vapor deposition. Keep other conditions the same as in Example 2 to obtain a copper particle catalyst supported on carbon nanofibers.

[0087] It was found that: the single-atom catalyst could not be obtained by omitting the graphite device. This indicates that in the absence of hierarchical management by the graphite device, copper metal atoms are prone to agglomeration and cannot achieve single-atom dispersion. The graphite device plays a crucial role in this process. It not only provides the necessary support structure but also maintains the uniformity of the atmosphere and temperature, which helps control the distribution of metal atoms on the carrier surface and prevents their agglomeration into particles. Therefore, omitting the graphite device will result in the inability to prepare a single-atom catalyst.

[0088] Comparative Example 3

[0089] Adjust the amount of PAN in Example 2 to 1 g, and keep the others the same as in Example 2 to obtain a copper particulate catalyst supported on carbon nanofibers.

[0090] It was found that: too little amount of PAN could not obtain the single-atom catalyst. When the amount of PAN decreases, the provided nitrogen source is not sufficient to coordinate fully with copper metal, resulting in the inability to achieve single-atom-level dispersion. In the synthesis of the single-atom catalyst, PAN serves as both a nitrogen source and a carbon source. It not only provides the structural carbon framework but also forms coordination bonds with metal atoms through its nitrogen-containing functional groups, which is crucial for stabilizing single-atom dispersion. Therefore, the reduction of PAN means the deficiency of coordination sites, and metal atoms are thus prone to agglomeration at high temperatures, forming larger particles and unable to form the required single-atom catalyst.

[0091] Comparative Example 4

[0092] Adjust the parameters of carbothermal reduction and chemical vapor deposition in Example 2 as follows: under an argon atmosphere, heat from 230 °C to 600 °C at a rate of 2 °C / min and hold for 4 h, then cool from 600 °C to room temperature under an argon atmosphere and cool at room temperature. Keep the others the same as in Example 2 to obtain a copper particulate catalyst supported on carbon nanofibers.

[0093] It was found that: when the temperature of carbothermal reduction and chemical vapor deposition is 600 °C, the temperature does not reach the temperature for complete atomic diffusion of copper particles, and the single-atom catalyst cannot be obtained. This phenomenon indicates that the temperature of 600 °C does not reach the vaporization point of copper particles, which is one of the necessary conditions for forming the single-atom copper structure. Thus, it can be seen that to achieve single-atom dispersion of copper atoms on the carrier, a higher temperature is required to promote the vaporization of copper particles and avoid their agglomeration on the surface of nanofibers. Therefore, an appropriate heat treatment temperature has a decisive influence on the preparation of the single-atom catalyst.

[0094] Comparative Example 5

[0095] Adjust the parameters of carbothermal reduction and chemical vapor deposition in Example 2 as follows: Under an argon atmosphere, heat from 230 °C to 1000 °C at a rate of 2 °C / min, and then directly cool from 1000 °C to room temperature under an argon atmosphere. Room temperature cooling is sufficient. Keep other conditions the same as in Example 2 to obtain a copper particle catalyst supported on carbon nanofibers.

[0096] It was found that omitting the constant temperature step in carbothermal reduction and chemical vapor deposition could not complete the full diffusion of copper atoms and a single-atom catalyst could not be obtained. The experimental results showed that such treatment failed to achieve the single-atom dispersion of copper atoms on the support. It can be inferred that the constant temperature stage is crucial for ensuring the dispersion of metal atoms because this step may provide a necessary time window for the uniform distribution and stable anchoring of metal atoms on the support surface. Therefore, without sufficient constant temperature holding time, copper atoms did not achieve the expected single-atom level dispersion on the surface of carbon nanofibers but formed larger particles, thus failing to produce a single-atom catalyst. This finding highlights the importance of controlling the constant temperature stage in the synthesis process and its impact on the final morphology and performance of the catalyst.

[0097] Example 3

[0098] Adjust the amount of CoCl2 in Example 2 to 1 mmol, and keep other conditions the same as in Example 2 to obtain a cobalt single-atom catalyst supported on carbon nanofibers.

[0099] Example 4

[0100] A method for synthesizing ammonia by nitrate reduction uses the single-atom catalysts with high metal loading and good atomic dispersion described in Examples 1, 2, and 3, and specifically includes the following steps:

[0101] (1) Mix 500 μL of isopropanol, 470 μL of ultrapure water, and 30 μL of 5% Nafion aqueous solution by mass to form a mixed solution; then disperse 3 mg of catalyst powder in the mixed solution and ultrasonically disperse for 1 h to obtain a homogeneous ink solution;

[0102] (2) Drop 5 μL of the ink solution onto a glassy carbon electrode with an area of 0.196 cm 2 such that the catalyst loading is precisely 0.0765 mg / cm 2 to obtain a glassy carbon electrode loaded with the catalyst;

[0103] (3) Use the glassy carbon electrode loaded with the catalyst, a platinum column as the counter electrode, and a Hg / HgO electrode as the reference electrode;

[0104] In 30 mL of 1 mol / L aqueous potassium hydroxide solution, different amounts of KNO were added to make the concentration of KNO be 10, 32.3, 100, 250, 500, and 1000 mM, obtaining electrolytes.

[0105] Before electrolysis, Ar was used to remove O and N in the environment. IT tests were carried out for 2 h to electrocatalytically reduce nitrate to ammonia, and finally a series of quantitative measurements were performed on ammonia.

[0106] After the reaction, performance tests were carried out, and the test results are as follows:

[0107] Table 1

[0108]

[0109] Example 5

[0110] The graphite device in Example 2 was adjusted to a ceramic device and a quartz device, and the others were kept the same as in Example 2, obtaining a copper single-atom catalyst.

[0111] The single-atom catalyst was tested by inductively coupled plasma optical emission spectrometry to evaluate the metal loading amount, and the results are shown in Table 2:

[0112] Table 2

[0113] Material Metal loading (%) Graphite (Example 2) 5.64 Ceramics 5.68 Quartz 5.47

[0114] It should be noted that for other types of polymers, such as polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP), due to their unique molecular structures and physicochemical properties, different metal salt ratios may be required. Therefore, although the present invention provides a specific ratio example, in actual applications, the ratio should be appropriately adjusted and optimized according to the type of polymer selected, the characteristics of the metal salt, and the performance requirements of the final nanofiber membrane. This flexibility is crucial for ensuring the excellent characteristics of the nanofiber membrane and the high performance of the final catalyst.

[0115] Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention should be defined by the claims.

Claims

1. A method for preparing a single-atom catalyst with a high metal loading and good atomic dispersion, characterized in that, It includes the following steps: (1) Mix a metal salt, a polymer and a solvent to obtain a spinning solution; then obtain a nanofiber membrane through electrospinning; wherein, the molar ratio of the metal salt to the polymer is 1:5 - 1:20; (2) Place the nanofiber membrane between two layers of high-temperature resistant devices for sealing treatment, carry out pre-oxidation, carbothermal reduction and chemical vapor deposition, and then take it out from the high-temperature resistant device to obtain a single-atom catalyst with a high metal loading and good atomic dispersion.

2. The method according to claim 1, wherein In step (1), the metal in the metal salt is one or more of iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, platinum, palladium, iridium, chromium, manganese, tungsten, vanadium, etc.; the polymer is one or several of flexible polymers such as polyester (PCL), polyamide (PA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylonitrile (PAN), etc.; the solvent is one or several of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), chloroform, tetrahydrofuran (THF), ethanol, water, etc.

3. The method according to claim 1, characterized in that, In step (1), the mass ratio of the polymer to the solvent is 1:5 - 20.

4. The method according to claim 1, wherein In step (2), the high-temperature resistant device is one of a graphite device, a quartz device, a ceramic device, etc.

5. The method according to claim 1, wherein In step (2), the high-temperature resistant device is sheet-shaped and forms a sandwich structure with the nanofiber membrane; the high-temperature resistant device and the nanofiber membrane can be laid at intervals to form a multi-layer structure.

6. The method according to claim 1, characterized in that, In step (2), the carbothermal reduction and chemical vapor deposition are carried out under the atmosphere of a protective gas by calcination treatment; specifically, the temperature is raised to 800 - 1200 °C at a rate of 2 - 10 °C / min and kept at a constant temperature for 1 - 5 h.

7. A single-atom catalyst with a high metal loading and good atomic dispersion prepared by the method according to any one of claims 1 - 6.

8. A method for synthesizing ammonia by nitrate reduction, characterized in that, The single-atom catalyst with a high metal loading and good atomic dispersion according to claim 7 is adopted.

9. Application of the single-atom catalyst with a high metal loading and good atomic dispersion according to claim 7 in the fields of electrolysis of water, reduction of carbon dioxide to prepare alcohols, reduction of nitrate to prepare ammonia or carbon-nitrogen coupling to prepare urea.

10. A method for improving the metal loading and uniformity of a single-atom catalyst, characterized in that, It includes the following steps: (1) Mix a metal salt, a polymer and a solvent to obtain a spinning solution; then obtain a nanofiber membrane through electrospinning; wherein, the molar ratio of the metal salt to the polymer is 1:5 - 1:20; (2) Place the nanofiber membrane between two layers of high-temperature resistant devices for sealing treatment, carry out pre-oxidation, carbothermal reduction and chemical vapor deposition, and then take it out from the high-temperature resistant device to obtain a single-atom catalyst with a high metal loading and good atomic dispersion.